Riffaterre's Semiotic Approach to Aḍḍamīru Al-’Arabī Song: Explores Lyrics as a Tool for Arab Integration - Bustam, Betty Mauli Rosa; Naf'an, Abdul Wahab (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2025)
This study examines the meaning of Arab unity as reflected in the lyrics of the song “Aḍḍamīru al-’Arabī” through the lens of Riffaterre’s semiotic approach. The song was selected due to its powerful symbolism in advocating Arab solidarity. Employing a descriptive qualitative method, the research analyzes the text and context of the lyrics to reveal hidden meanings, ideologies, and symbolic messages. The analysis follows several stages: heuristic and hippogram identification, indirect expression analysis, and retrospective reading. The findings indicate that the song serves not only as a work of art but also as a political instrument in fostering solidarity amidst the Middle East conflict. This study contributes to the field of semiotic analysis and offers a new perspective on the intersection of music and politics within the scope of cultural diplomacy. مستخلص تبحث هذه الدراسة معنى الوحدة العربية كما تتجلى في كلمات أغنية